On Surfaces in Pseudo-Galilean Space with Prescribed Mean Curvature - Aydin, Muhittin Evren; Öğrenmiş, Alper Osman (Adiyaman University, 2021)
In this study, we consider certain classes of surfaces in the pseudo-Galilean space, the translation and factorable surfaces. We obtain these surfaces that satisfy the equation H = v!, where H is the mean curvature and v! is the normal component of an isotropic vector v. © 2021, Adiyaman University. All rights reserved.
Yarı-Galileo Uzayında Belli Bir Ortalama Eğriliğe Sahip Yüzeyler Üzerine
Keywords: Manifolds with density; Mean curvature; Pseudo-Galilean space; Translating soliton